Analyzing Knowledge Networks in Health Care through Collaborative Research Exploration - Diki Prayugo Wibowo; Ria Mariani; Novian Aldo; Sulistyo Andarmoyo (West Science Interdisciplinary Studies, 2023)
The exploration of collaborative research in healthcare is a dynamic and multifaceted endeavor, as evidenced by analysis of influential articles, citation patterns, and keyword frequencies. Davenport and Prusak's seminal work on knowledge management serves as a foundational foundation, emphasizing the critical role of effective knowledge utilization and sharing in collaborative healthcare research. This research explores linkages with other influential articles, including Scott's examination of social network analysis, Star and Griesemer's insights on institutional ecology, and Tranfield et al.'s methodology on evidence-based knowledge management. Further analysis extends to works on thematic analysis, inter-organizational collaboration, cancer genomics, and qualitative research methods, all of which contribute to a rich tapestry of collaborative healthcare research. Keyword analysis revealed thematic priorities, with a major focus on "Care" and "Experience", emphasizing the human dimension of healthcare. Challenges, technology and organizational aspects emerged as prominent themes, reflecting a holistic approach to collaborative exploration. The interplay between keywords such as "Dynamic", "Mechanisms", and "Performance" underscores the evolving nature of collaborative efforts and the need for strategic mechanisms to address challenges and improve performance. The analysis also highlights contemporary concerns, including the impact of the COVID-19 pandemic, barriers to collaboration, and the intersection of mental health and social media.